Biomass Profiling in a Horizontal-Flow Anaerobic Bioreactor Used for Limonene Degradation - Pozzi, Eloisa; Motteran, Fabricio; de Mello, Bruna Sampaio [UNESP]; Rodrigues, Brenda Clara Gomes [UNESP]; Sarti, Arnaldo [UNESP] (Springer Nature, 2024)
This study characterized the microbial community present in the bench scale horizontal-flow anaerobic immobilized biomass bioreactor (HAIB) used in the removal of limonene, a compound present in citrus processing industries. The HAIB was filled with three support materials (coal, polyurethane foam and gravel) which were inoculated with anaerobic sludge. The limonene initial concentration on the substrate ranged from 10 mg/L to 500 mg/L. The analysis of 16S rRNA showed the presence of 22 OTUs (based on ⩾97% sequence identity), distributed in 57 genera, considering three different matrices. Higher relative abundance of phyla was observed as Synergistetes (43–57%), Proteobacteria (32–42%), Firmicutes (7–8%) and Acidobacteria (2–3%). Actinobacteria, Bacterioidetes and Chloroflexi had the lowest relative abundances between 1 and 2%. Synergistaceae family was the predominated group (47.6%—mineral coal, 55.9%—foam and 43.5%—gravel) followed by Syntrophaceae (2.4%—coal, 1.5%—foam and 2.2%—gravel), which kept a syntrophic relationship with methanogenesis (hydrogenotrophic methanogens) to maintain the anaerobic digestion. Among the Proteobacteria phylum, the Pseudomonadaceae family was predominant in the system with 12.0% on coal, 13.1% on foam, and 20.4% on gravel. The metabolic versatility of Pseudomonas sp. makes them an important bioremediation agent by being capable of metabolizing xenobiotic and chemical toxic compounds, thus having great prominence for the limonene removal in the HAIB bioreactor.